Risk factors affecting prognosis in metachronous liver metastases from WHO classification G1 and G2 gastroenteropancreatic neuroendocrine tumors after initial R0 surgical resection - Yang Lv; Xu Han; Xue-Feng Xu; Yuan Ji; Yu-Hong Zhou; Hui-Chuan Sun; Jian Zhou; Jia Fan; Wen-Hui Lou; Cheng Huang (BMC Cancer, 2019)
Abstract Background Here we describe the treatments and prognosis for metachronous metastases from gastroenteropancreatic neuroendocrine tumors (GEP-NETs) after initial R0 surgical resection at a large center in China. Methods The clinicopathological data and survival outcomes for 108 patients (median age, 54.0 years) with metachronous hepatic metastatic GEP-NETs disease who were initially treated using R0 surgical resection between August 2003 and July 2014 were analyzed using one-way comparisons, survival analysis, and a predictive nomogram. Results Fifty-five (50.9%) patients had pancreatic NETs and 92 (85.2%) had G2 primary tumors. For treatment of the hepatic metastases, 48 (44.4%) patients received liver-directed local treatment (metastasectomy, radiofrequency ablation, transcatheter arterial chemoembolization, etc.), 15 (13.9%) received systemic treatment (interferon, somatostatin analogs, etc.), and 45 (41.7%) received both treatments. Multivariable analyses revealed that OS was associated with hepatic tumor number (P < 0.001), treatment modality (P = 0.045), and elevated Ki-67 index between the metastatic and primary lesions (P = 0.027). The predictive nomogram C-index was 0.63. Conclusions A higher Ki-67 index in metastases compared to primary tumor was an independent factor for poor prognosis. Local treatment was associated with prolonged survival of hepatic metastatic GEP-NET patients. Optimal treatment strategies based on clinicopathological characteristics should be developed.